2003
DOI: 10.1038/sj.bjc.6600992
|View full text |Cite
|
Sign up to set email alerts
|

Clinical aspects of a phase I trial of 5,6-dimethylxanthenone-4-acetic acid (DMXAA), a novel antivascular agent

Abstract: The antitumour action of 5,6-dimethylxanthenone-4-acetic acid (DMXAA) is mediated through tumour-selective antivascular effects and cytokine induction. This clinical phase I trial was conducted to examine its toxicity, maximum tolerated dose, pharmacokinetics (PK) and pharmacodynamics (PD). A secondary objective was to assess its antitumour efficacy. DMXAA was administered every 3 weeks as a 20-min i.v. infusion. Dose escalation initially followed a modified Fibonacci schema but was also guided by PK and toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
125
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(132 citation statements)
references
References 42 publications
7
125
0
Order By: Relevance
“…There was one unconfirmed partial response at 1300 mg m À2 . In a second study, in which 63 patients received 3-weekly infusions, comparable DLTs were observed with additional confusion, slurred speech, tremor and possible left ventricular failure (Jameson et al, 2003). Asymptomatic transient QTcprolongation was seen in 13 patients at high doses.…”
Section: Flavonoids Dmxaamentioning
confidence: 81%
“…There was one unconfirmed partial response at 1300 mg m À2 . In a second study, in which 63 patients received 3-weekly infusions, comparable DLTs were observed with additional confusion, slurred speech, tremor and possible left ventricular failure (Jameson et al, 2003). Asymptomatic transient QTcprolongation was seen in 13 patients at high doses.…”
Section: Flavonoids Dmxaamentioning
confidence: 81%
“…DMXAA was dissolved directly in culture medium for in vitro experiments. In the clinical phase trial conducted in Auckland, New Zealand, DMXAA was administered as a 20 min intravenous infusion on a 3-weekly schedule, using a pre-formulated solution of 20 mg ml 71 in 0.1 M phosphate buffer at pH 7.7 (Jameson et al, 2000). maintained under constant temperature and humidity according to institutional ethical guidelines and used between 8 -12 weeks of age.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the large increases in plasma TNF observed in mice treated with DMXAA, plasma TNF levels in patients treated in a Cancer Research UK phase I trial were not elevated (Jameson et al, 2000). However, dynamic contrast-enhanced magnetic resonance imaging suggested that tumour blood flow was inhibited in most patients receiving DMXAA at doses of 500 mg m 72 or higher (Rustin et al, 1998).…”
mentioning
confidence: 99%
“…DMXAA is known to induce interferons (Pang et al, 1998), IP-10 (Cao et al, 2001), serotonin (Baguley et al, 1993(Baguley et al, , 1997 and nitric oxide (Thomsen et al, 1991). Phase I trials of DMXAA show evidence of decreased tumour blood flow (Rustin et al, 1998;Jameson et al, 2000) and increased plasma 5HIAA ), but only a small increase in plasma nitrate and no increase in plasma TNF (Jameson et al, 2000). It is possible that other DMXAA-inducible cytokines are involved in humans, and their identification is an important consideration in future clinical trials.…”
Section: Experimental Therapeuticsmentioning
confidence: 99%
“…Flavone-8-acetic acid (FAA), and its more potent analogue 5,6-dimethylxanthenone-4-acetic acid (DMXAA), developed in this laboratory, are low molecular weight antivascular agents that appear to exert their antitumour effects at least partly through the induction of TNF (Mace et al, 1990;Philpott et al, 1995). FAA proved to be inactive in clinical studies (Kerr and Kaye, 1989), but DMXAA has shown evidence of activity in a Phase I clinical trial (Jameson et al, 2000).…”
mentioning
confidence: 99%